2009
DOI: 10.1007/s12011-009-8469-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Trace Elements in the Scalp Hair of Malignant and Benign Breast Lesions Versus Healthy Women

Abstract: Trace elements including Al, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, Sb, Sr, and Zn were analyzed in the scalp hair samples of women with malignant breast lesions, women with benign breast lesions, and healthy donors using atomic absorption spectrophotometric method. In the scalp hair of malignant-tumor patients, the highest average concentration was shown by Ca (1,187 microg/g), followed by Na (655 microg/g), Mg (478 microg/g), Zn (391 microg/g), Sr (152 microg/g), Fe (114 microg/g), and K (89.8), whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
(36 reference statements)
0
19
0
1
Order By: Relevance
“…One small case-control study (n = 52 cases and 52 controls) reported statistically higher levels of antimony in hair of stage III breast cancer patients compared with healthy controls [43]. In a different case-control study including women with malignant breast cancer (n = 33), benign breast disease (n = 36), and healthy controls (n = 35), Sb levels were higher in the scalp hair of the benign group, and malignant group compared with the controls; however, levels were considerably higher in women with benign lesions [35]. Interestingly, Choe et al [44] were the first to suggest that along with other major heavy metals, Sb exhibits estrogenic activity and may function as an environmental endocrine disrupter influencing carcinogenesis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One small case-control study (n = 52 cases and 52 controls) reported statistically higher levels of antimony in hair of stage III breast cancer patients compared with healthy controls [43]. In a different case-control study including women with malignant breast cancer (n = 33), benign breast disease (n = 36), and healthy controls (n = 35), Sb levels were higher in the scalp hair of the benign group, and malignant group compared with the controls; however, levels were considerably higher in women with benign lesions [35]. Interestingly, Choe et al [44] were the first to suggest that along with other major heavy metals, Sb exhibits estrogenic activity and may function as an environmental endocrine disrupter influencing carcinogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, we reported a significant inverse relationship between circulating iron levels and breast cancer risk among BRCA1 mutation carriers. Notably, Pasha et al [35] reported significantly higher iron levels in the scalp of healthy controls compared with women with malignant breast cancer or benign breast disease. Quantifying levels of heavy metal in hair samples have been suggested to accurately reflect long-term exposure [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Mean concentrations of Ca, Cd, Co, K, Mg, Mn, Na, Ni, Pb, Sb, Sr and Zn are significantly higher in the hair of benign tumour patients than normal donors. The results of correlation analysis, principal component analysis and cluster analysis evidenced significantly different patterns of metal distribution in hair of benign tumour patients in comparison with normal donors [17,21]. In human serum, a significant difference in concentrations of all metals between breast cancer patients and controls are observed [34].…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, trace element in human hair has been considered as a tool for routine clinical screening and diagnosis of many diseases [13]. In recent years, many investigations have been conducted to determined contents of trace elements in hair of patients, such as malignant and benign breast lesions, autism, obesity and diabetes, myocardial infarction patients, benign tumor patients, hypertensive patients, gastrointestinal cancer patients, prostate cancer patients, cerebral palsy patients, respiratory system diseases patients [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the hair was chosen as a sample to study the trace elements in the human body by some researchers because the hair was obtained easier, and the trace elements were accumulated in it. In the previous works, they have researched the pollution accumulation in the environment [1][2][3][4][5][6][7][8], the environmental effects on human health [9][10][11], trace elements effects on human health [12][13][14][15][16], and the objects and results were different for the different research. Jinzhou is located at the southwest of Liaoning province in China.…”
Section: Introductionmentioning
confidence: 99%